Life expectancy in Iraq from 1950 to 2024: A retrospective time-series analysis - Ahmed, Darya R. (Narra Sains Indonesia, 2025)
Life expectancy is a vital demographic indicator reflecting the health and well-being of a population. The aim of this study was to analyze life expectancy trends in Iraq from 1950 to 2024 using Worldometer data aggregated from United Nations statistics. The Iraqi population increased from 6.37 million in 1955 to 46.04 million in 2024, representing a 623% increase, with urbanization rising from 38.4% to 71.8%. Fertility rates declined from 6.0 live births per woman in 1955 to 3.2 in 2024, peaking at 7.1 in 1970 before steadily decreasing. Life expectancy improved significantly from 37.4 years in 1950 to 72.4 years in 2024, with a narrowing gender gap: life expectancy for men increased from 34.3 years in 1950 to 70.5 years in 2024, while for women, it rose from 41 years to 74.2 years over the same period. The median age also increased slightly, from 19.5 years in 1955 to 20.6 years in 2024. Infant mortality rates dropped dramatically, from 206.6 deaths per 1,000 live births in 1950 to 18.7 in 2024, and under-five mortality fell from 357.9 to 22.4. Despite historical conflicts, improvements in healthcare and living conditions highlight Iraq’s dynamic demographic changes, presenting the ongoing challenges and opportunities posed by its rapid growth and urbanization.